The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Correction to: Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

Enhancing Efavirenz Bioavailability Via Polymer-Based Buccal Administration: Optimization and Characterization of Nanocrystal-Loaded Dissolving Microneedle Delivery Systems - Khairiyah Khairiyah; Muh. Bisfain Asaf; Nur Afni Annisa Achmad; Rachmatya W. Tuna; Irfan Kurniawan; Anugerah Yaumil Ramadhani Aziz; Maria Mir; Juan Domínguez-Robles; Mónica Millán-Jiménez; Ilyas Essadki-Aittaji; Ana B. Cobo-González; Muhammad Aswad; et al. (The AAPS Journal, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Assemblages of planktonic cnidarians in winter and their relationship to environmental conditions in the NW Mediterranean Sea - Marina Pastor-Prieto; Vanesa Raya; Ana Sabatés; Elena Guerrero; Joan Mir-Arguimbau; Josep-Maria Gili (Journal of Marine Systems, 2024)

Electroporation Transiently Decreases GJB2 (Connexin 26) Expression in B16/BL6 Melanoma Cell Line - Marcelo Monte Mór Rangel; Lucas Martins Chaible; Marcia Kazumi Nagamine; Gregory Mennecier; Bruno Cogliati; Krishna Duro de Oliveira; Heidge Fukumasu; Idércio Luiz Sinhorini; Lluis Maria Mir; Maria Lúcia Zaidan Dagli (The Journal of Membrane Biology, 2015)

Application of Crustacean Chitin as a Co-diluent in Direct Compression of Tablets - Viviana García Mir; Jyrki Heinämäki; Osmo Antikainen; Niklas Sandler; Ofelia Bilbao Revoredo; Antonio Iraizoz Colarte; Olga Maria Nieto; Jouko Yliruusi (AAPS PharmSciTech, 2010)

Neuroprotective Role of Antidiabetic Drug Metformin Against Apoptotic Cell Death in Primary Cortical Neurons - Mohamad-Yehia El-Mir; Dominique Detaille; Gloria R-Villanueva; Maria Delgado-Esteban; Bruno Guigas; Stephane Attia; Eric Fontaine; Angeles Almeida; Xavier Leverve (Journal of Molecular Neuroscience, 2008)